Digital platform solutions of Russian Railways as a tool for the development of the concept of MaaS (Mobility as a Service) - Gulyi Ilia; Shavurskaya Viktoriya (E3S Web of Conferences, 2023)
The purpose of the study: to substantiate the advantages of the Maas (Mobility as a Service) concept as a universal digital Smart aggregator, a platform integrating all participants in passenger transportation. Methods: content analysis, analysis of digital platform technologies, monitoring of digital processes and solutions at the level of a separate transport company. Results: the main advantages of digital transport multimodality as a concept of integrated digital platforms of the future transport are substantiated. The hypothesis is put forward that electronic digitalized communication technologies of market participants will become the main factor of economic growth. And the ideal MaaS-economic model will be a comprehensive integration of all existing digital platforms in the world and on national markets. The functionality and advantages for users of the development of MaaS solutions of the Russian railway carrier - the Russian Railways company — the Travel.RZD application and a pilot project within the framework of Innovative mobility implemented in the Samara region are presented.